Alanine, a Novel Growth Substrate for the Acetogenic Bacterium Acetobacterium woodii - Dönig, Judith (Appl Environ Microbiol, 2018)
Acetogenic bacteria are an ecophysiologically important group of strictly anaerobic bacteria that grow lithotrophically on H(2) plus CO(2) or on CO or heterotrophically on different substrates such as sugars, alcohols, aldehydes, or acids. Amino acids are rarely used. Here, we describe that the model acetogen Acetobacterium woodii can use alanine as the sole carbon and energy source, which is in contrast to the description of the type strain. The alanine degradation genes have been identified and characterized. A key to alanine degradation is an alanine dehydrogenase which has been characterized biochemically. The resulting pyruvate is further degraded to acetate by the known pathways involving the Wood-Ljungdahl pathway. Our studies culminate in a metabolic and bioenergetic scheme for alanine-dependent acetogenesis in A. woodii. IMPORTANCE Peptides and amino acids are widespread in nature, but there are only a few reports that demonstrated use of amino acids as carbon and energy sources by acetogenic bacteria, a central and important group in the anaerobic food web. Our finding that A. woodii can perform alanine oxidation coupled to reduction of carbon dioxide not only increases the number of substrates that can be used by this model acetogen but also raises the possibility that other acetogens may also be able to use alanine. Indeed, the alanine genes are also present in at least two more acetogens, for which growth on alanine has not been reported so far. Alanine may be a promising substrate for industrial fermentations, since acid formation goes along with the production of a base (NH(3)) and pH regulation is a minor issue.